2013
DOI: 10.2478/johr-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Development of Potted Rhododendron Cultivars ‘Catawbiense Boursault’ and ‘Old Port’ in Response to Regulated Deficit Irrigation

Abstract: The aim of this study was to analyse the effect of regulated deficit irrigation (RDI) on growth and development of potted rhododendron ‘Catawbiense Boursault’ and ‘Old Port’ plants and to evaluate the usefulness of this technique for saving water in nursery production and promoting flowering. Plants were grown in 1.9 litre plastic containers in unheated greenhouse and were subjected to six irrigation treatments lasting for 14 weeks from June to mid-September. A drip irrigation system with one 2 dm3·h-1 emitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Leaf area and number of leaves were 36% lower for drought-stressed than for well-watered plants (P = 0.012 and P = 0.016, respectively; Table 1), but the average leaf size was unaffected by drought (Table 1). Reduced leaf area with drought stress has been reported for G. lindheimeri (Burnett and van Iersel, 2008), Rhododendron 'Catawbiense Boursault' and Rhododendron 'Old Port' (Koniarski and Matysiak, 2013), S. splendens (Burnett et al, 2005), and T. erecta (van Iersel and Nemali, 2004). Leaf size of H. acetosella 'Panama Red' was reduced with decreasing substrate volumetric water content (Bayer et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Leaf area and number of leaves were 36% lower for drought-stressed than for well-watered plants (P = 0.012 and P = 0.016, respectively; Table 1), but the average leaf size was unaffected by drought (Table 1). Reduced leaf area with drought stress has been reported for G. lindheimeri (Burnett and van Iersel, 2008), Rhododendron 'Catawbiense Boursault' and Rhododendron 'Old Port' (Koniarski and Matysiak, 2013), S. splendens (Burnett et al, 2005), and T. erecta (van Iersel and Nemali, 2004). Leaf size of H. acetosella 'Panama Red' was reduced with decreasing substrate volumetric water content (Bayer et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…Drought stress has been used to reduce elongation in many species including Gaura lindheimeri Engelm. & Gray 'Siskiyou Pink' (Burnett and van Iersel, 2008), Rhododendron 'Catawbiense Boursault' and Rhododendron 'Old Port' (Koniarski and Matysiak, 2013), Tagetes erecta L. 'Queen Sophia' (van Iersel and Nemali, 2004), Salvia splendens F. Sellow. Ex Roem.…”
Section: Resultsmentioning
confidence: 99%
“…Plant appearance is important to consumers, with consumers associating appearance with overall plant health [5] and poor plant form or uniformity resulting in reduced sales [6]. Uneven plant growth can be the result of irrigation practices, pruning, or plant growth regulation applications.…”
Section: Introductionmentioning
confidence: 99%
“…After the end of this experimental part of the study, shrubs were left in an unheated greenhouse and each container with plant was irrigated with 300 ml of water. The methodology concerned this stage of study was the same as in study of Koniarski and Matysiak [2013] and this is the continuation of that research.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…In 2012, experiments were conducted whose aim was to analyse the effect of regulated deficit irrigation (RDI) on growth and development of potted rhododendron 'Catawbiense Boursault' and 'Old Port' plants [ Koniarski and Matysiak 2013]. Those studies found that moderate and severe water deficit maintained throughout the 14-week period of growing of shrubs Rhododendron 'Catawbiense Boursault' and 'Old Port' as well as severe water deficit applied only during the vegetative growth limits the elongation growth of shoots, improves plant habit and quality.…”
Section: Introductionmentioning
confidence: 99%